Penerapan Pendekatan Saintifik Melalui Model Pembelajaran Kooperatif Tipe Jigsaw Di Kelas X SMA Negeri 9 Palu Pada Materi Stoikiometri - Saldi, Heri; Nuryanti, Siti; Sakung, Jamaluddin (Universitas Tadulako, 2017)
This study aims to determine the influence of implementation a scientific approach through cooperative-jigsaw learning model on Stoichiometry to the learning achievement of students in class X at SMAN 9 Palu. The method was a quasi experiment with pretest-posttest control group design. The population was students of class X SMA Negeri 9 Palu, where the sample was class XB as the experimental group (n = 29) and class XA as the control group (n = 27), determined by purposive sampling technique. Data were analyzed using nonparametric statistical Mann-Whitney U-Test analysis. The results showed output â€œRankâ€ for the mean value of the experimental class was greater than the control class, 33.14 Ëƒ 23.52. The output of â€œTest Statisticsâ€, Sig. 2-Tailed (0,026) Ë‚ 0.05 and Zcount(-2.23) Ë‚ Ztable (-1.96), as well as each classical completeness and absorption for experimental class were 79% and 83%, while for the control class were 59% and 75%. This study concluded that scientific approach through cooperative-jigsaw model on Stoichiometry influenced positively to the learning achievement of students in class X at SMA Negeri 9 Palu.